Case Report: Metagenomic Next-Generation Sequencing in Diagnosis of Disseminated Tuberculosis of an Immunocompetent Patient - Ye, Yuanting; Yang, Naibin; Zhou, Jingying; Qian, Guoqing; Chu, Jinguo (Frontiers in Medicine, 2021)
Disseminated tuberculosis (TB) is a rare disease and mainly occurs in immunodeficient patients. It is marked by hematogenous or lymphatic dissemination of Mycobacterium tuberculosis, causing tuberculous infection involving any organ system. Here, we report a case of disseminated TB involving lung, liver, spine, mediastinum, and prostate in an immunocompetent man. The present patient found a hepatic mass without any symptom during health examination. In the next 2 years, further examinations revealed multiple lesions in the lung, liver, spine and prostate. Imaging examinations, such as contrast-enhanced abdominal CT, F-18 FDG-PET/CT, and radionuclide bone scan, suggested the diagnosis of malignancy or metastatic tumor. Furthermore, histopathological results of the biopsies of the hepatic mass, mediastinal mass, and prostatic mass demonstrated granulomatous inflammation. Therefore, metagenomic next-generation sequencing (mNGS) was utilized to confirm the diagnosis. Mycobacterium tuberculosis complex was simultaneously detected in the spinal surgical resection specimens and bronchoalveolar lavage fluid (BALF), indicating the diagnosis of disseminated TB. mNGS is an emerging molecular diagnostic technology and its application in disseminated TB has been rarely reported. We highlight that disseminated TB should be considered even in an immunocompetent patient and mNGS can be performed when the diagnosis is difficult.